The need for a new master’s program of applied computer science to cope with future demands of the industry - Rababaah, Aaron (2021)
This paper presents a local study in the State of Kuwait to investigate the need for a new master program in applied computer science. It is evident that science and technology are trending towards some high-interest areas including machine learning, robotics, information security and big data. Bedsides government and industry, educational institutions are at the frontline of this revolution and they have the responsibility to lead the efforts in building reliable workforce for the future. Therefore, we have completed a comprehensive study to investigate the need for a new master's program that fits the context of the aforementioned situation. The new program is called Master of Applied Computer Science - MACS. The program is proposed to offer three tracks that best utilise the needed expertise and align with the current and future demands of the domestic market; these tracks are: mobile robotics, information security and software engineering. Three surveys for current students, alumni and employers were conducted and analysed and their findings were discussed in this work. We are confident that master programs developers in Kuwait will significantly benefit from this study to maximise their opportunities of success.